Social Stigma: The Hidden Threat of COVID-19 - Abdelhafiz, Ahmed Samir; Alorabi, Mohamed (Frontiers in Public Health, 2020)
COVID-19 infection has been recognized as a pandemic by the World Health Organization. Efforts to prevent the spread of the disease are threatened by the appearance of disease-associated social stigma in society. In Egypt, a small wave of stigma directed at different groups started to appear. Here we report the features of COVID-19-associated stigma in Egypt and suggest recommendations to overcome this stigma before it grows and have physical and psychological impacts on society.